2022
DOI: 10.1016/j.asmr.2021.09.037
|View full text |Cite
|
Sign up to set email alerts
|

Unique Considerations for the Pediatric Athlete During Rehabilitation and Return to Sport After Anterior Cruciate Ligament Reconstruction

Abstract: Anterior cruciate ligament (ACL) injuries and surgical intervention in the pediatric population have increased in the recent years. Although surgical techniques have advanced, evidence-based rehabilitation guidelines that consider all aspects of the youth athlete are currently lacking. The purpose of this commentary is to review the current evidence on unique considerations for the pediatric and adolescent population during rehabilitation and return to sport after ACL reconstruction (ACLR), with a focus on chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 134 publications
1
14
0
Order By: Relevance
“…Failure of r-ACLR represents a significant issue in paediatric and adolescent patients. In addition to its acute physical and psychosocial impacts [50]. Particularly, chronic ACL-deficiency has been suggested to accelerate the development of osteoarthritis, a devastating consequence for young patients [51][52][53].…”
Section: Discussionmentioning
confidence: 99%
“…Failure of r-ACLR represents a significant issue in paediatric and adolescent patients. In addition to its acute physical and psychosocial impacts [50]. Particularly, chronic ACL-deficiency has been suggested to accelerate the development of osteoarthritis, a devastating consequence for young patients [51][52][53].…”
Section: Discussionmentioning
confidence: 99%
“…Patients' descriptions of feelings include: burden, worry, frustration, hopelessness, devastation, and isolation. 23,30,36,52,68 Mental health conditions, such as anxiety and depression, may increase in severity in response to injury and be detrimental to outcomes. 46 Schaffer et al 58 observed outcomes of patients stratified into 3 cohorts: clinical diagnosis of depression, situational depression, and no depression.…”
Section: Impact Of Injury Experiencementioning
confidence: 99%
“…25,68 Patients are further dissatisfied when shown a lack of attention and/or generalized treatment. 36 Patients and their families report educational resources and consistent communication would better the experience, allowing collaborative decision-making and supportive care. 25,33,53,68 The support system need not come only from rehabilitation care providers; larger support networks (eg, friends, family, teammates, care providers, coaches, fans, online support groups) promote positive recovery experiences.…”
Section: Impact Of Injury Experiencementioning
confidence: 99%
“… 71 , 72 , 76 Another indication for AEAPs in the pediatric setting may be very young children who have a limited rehabilitation capacity and poor neuromuscular control. 77 …”
Section: Aeapsmentioning
confidence: 99%
“…71,72,76 Another indication for AEAPs in the pediatric setting may be very young children who have a limited rehabilitation capacity and poor neuromuscular control. 77 Pediatric cadaveric studies have shown some improvements in translation or rotatory instability with AEAPs but clinical outcome data are lacking in the skeletally immature. 28 The adult literature does support the use of AEAPs with which there has been improved graft failure rates regardless of AEAP method, better outcome scores, and patient satisfaction.…”
Section: Aeapsmentioning
confidence: 99%